The emerging role of inorganic elements as potential antigens in sarcoidosis. Issue 5 (September 2021) - Beijer, Els; Veltkamp, Marcel
Abstract : Purpose of review: Previous studies mainly described a role for organic agents as possible triggers for sarcoidosis. In this review, we address recent studies suggesting a possible role for inorganic elements, such as metals or silica in sarcoidosis pathogenesis. Recent findings: Several epidemiological papers suggest that inorganic agents, either by environmental exposures or occupational activities, could trigger sarcoidosis. Association between inorganics and sarcoidosis is also described in several recently published case reports and studies demonstrating immunological sensitization to inorganic agents in sarcoidosis patients. Studies comparing chronic beryllium disease (CBD) and sarcoidosis suggest that although antigenic triggers may differ, underlying processes may be comparable. Besides the fact that a growing number of studies show a possible role for inorganic triggers, it is also suggested that inorganic triggered sarcoidosis may result in a more severe phenotype, including pulmonary fibrosis. Summary: We can use the knowledge already gained on CBD pathogenesis to conduct further research into role of inorganics, such as metals and silica as antigens in sarcoidosis. Given the importance of a lymphocyte proliferation test (LPT) in diagnosing CBD, it seems obvious to also implement this test in the diagnostic work-up of sarcoidosis to identify patients with an inorganic antigenic trigger of their disease.